The influence of soccer-specific exercise on isokinetic angle-specific thigh musculature strength in female soccer players - Eustace, S. J.; Alderman, K.; Murray, K.; Tallis, J.; Myers, T.; Page, R. M. (Journal of Sports Sciences, 2025)
This study assessed the influence of soccer-specific exercise on thigh musculature strength in female soccer players. Eight amateur female soccer players (age 24 ± 6 years; height 163 ± 8 cm; mass 68 ± 11 kg) participated in the study. Participants completed the female match simulation-90 (FEMS-90), replicating a 90-minute match. Isokinetic strength assessments of the concentric knee extensors (conKE), concentric knee flexors (conKF), eccentric knee extensors (eccKE) and eccentric knee flexors (eccKF) for the dominant lower limb were conducted at 60°·s-1 where conventional ratios (CR) and dynamic control ratios (DCR) were determined. All strength data were expressed as angle-specific torque (AST). A Bayesian approach identified a 66-78% probability that AST of all muscle actions were lower post SSEP, and a 57-66% probability of a difference that CRAST and DCRAST were lower post SSEP across all angles. The results of this study provides unique insight into how female soccer players respond to soccer match-play, and may have implications for potential injury risk, exercise prescription and recovery. Moreover, given the prevalence and burden of knee ligament injuries in female soccer players, this study provides insight into thigh musculature strength acutely responds following simulated match-play.